2002
DOI: 10.1006/jfan.2001.3900
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Improved Hardy Inequalities

Abstract: Let O be a bounded domain in R N ; N 53, containing the origin. Motivated by a question of Brezis and V! a azquez, we consider an Improved Hardy Inequality with best constant b, that we formally write as: ÀD5ð NÀ22 Þ 2 1 jxj 2 þ bV ðxÞ. We first give necessary conditions on the potential V , under which the previous inequality can or cannot be further improved. We show that the best constant b is never achieved in H 1 0 ðOÞ, and in particular that the existence or not of further correction terms is not connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
186
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(192 citation statements)
references
References 10 publications
6
186
0
Order By: Relevance
“…So, one could anticipate improving this inequality by adding a nonnegative correction term to the right-hand side of the inequality shown as Eq. 1, and indeed, several sharpened Hardy inequalities have been established in recent years (3,5), mostly triggered by the following improvement of Brezis and Vázquez (1). For all u in H 1 0 ( ),…”
mentioning
confidence: 99%
“…So, one could anticipate improving this inequality by adding a nonnegative correction term to the right-hand side of the inequality shown as Eq. 1, and indeed, several sharpened Hardy inequalities have been established in recent years (3,5), mostly triggered by the following improvement of Brezis and Vázquez (1). For all u in H 1 0 ( ),…”
mentioning
confidence: 99%
“…In analogy with the results of [10] and [16], it is then natural to ask whether one can make subcritical or critical Sobolev improvements to the inequality (1.5) via finding lower bounds for I n [u; Ω]. Here we enter into another type of criticality, where the Sobolev critical exponent is formally +∞.…”
Section: Hardy-sobolev Inequalitymentioning
confidence: 98%
“…Actually, it is well known that I[u; Ω] > 0 if u ∈ W 1,2 0 (Ω)\{0}, which suggests the possibility of improving the inequality (1.1) in the form of lower bounds for I[u; Ω]. While for Ω = R n it has been shown that additional correction terms cannot be added (see for example [16], [19] & [14]), if Ω has finite volume such an improvement is possible. The following subcritical Sobolev improvement of the Hardy inequality (1.1) is due to Brezis and Vazquez [10]: If Ω has finite volume, then for any 1 ≤ q < 2 * , there exists C n,q > 0 depending only on n and q, such that I[u; Ω] 1/2 ≥ C n.q vol(Ω) 1/q−1/2 * Ω |u| q dx 1/q for all u ∈ C ∞ c (Ω).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was observed by Brezis and Vázquez [8] and others [24] that the inequality can be improved. The story here is the link-discovered by Ghoussoub and Moradifam [26,27]-between various improvements of this inequality confined to bounded domains and Sturm's theory regarding the oscillatory behavior of certain linear ordinary equations.…”
Section: To See Thatmentioning
confidence: 99%